Perinatal nutrition programs neuroimmune function long-term: mechanisms and implications - Spencer, Sarah J. (Frontiers in Neuroscience, 2013)
Our early life nutritional environment can influence several aspects of physiology, including our propensity to become obese. There is now evidence to suggest perinatal diet can also independently influence development of our innate immune system. This review will address three not-necessarily-exclusive mechanisms by which perinatal nutrition can program neuroimmune function long-term: by predisposing the individual to obesity, by altering the gut microbiota, and by inducing epigenetic modifications that alter gene transcription throughout life.